Inhibition of Fish Bacterial Flora by Bacteriocin of Lactic Acid Bacteria - D., Panchayuthapani; T., Jawahar Abraham; P., Jeyachandran (Fishery Technology, 2025)
Seven strains of lactic acid bacteria (LAB) were tested for the production of bacteriocins or bacteriocin-like substances by the agar spot method. By excluding inhibition due to acid and confirming their proteinaceous nature, the inhibitors were confirmed as bacteriocins. The ability of four bacteriocin producing strains, viz., Lactobacillus plantarum 89, L. plantarum 8014, L. helveticus, and Pediococcus pentosaceus 25445, to inhibit thirty-five strains of bacteria isolated from fish and fishery products were screened. Strains of Enterococcus spp. and Flavobacterium/Cytophaga were inhibited by bacteriocins of LAB. Vibrio parahaemolyticus was inhibited slightly by bacteriocins of L. plantarum 89 and P. pentosaceus 25445. Aeromonas hydrophila, Salmonella sp. and V. cholerae were not inhibited. The bacteriocins of LAB are bactericidal to 42 to 54% of the fish microflora tested.